2020
DOI: 10.1186/s43044-020-00120-x
|View full text |Cite
|
Sign up to set email alerts
|

The changes in biventricular remodelling and function after atrial septal defect device closure and its relation to age of closure

Abstract: Background The trans-catheter closure of atrial septal defect (ASD) usually has a rapid impact on biventricular remodelling and functions. Whether the transcatheter closure of ASD at early childhood or at adulthood age would affect the improvement in biventricular dimensions and functions remains an area of active research. Results This prospective observational study enrolled 70 subjects (50 ASD cases and 20 control subjects). Tissue Doppler imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…17 A recent study published in 2020 reported reduced RV global longitudinal strain and an early decline in LV global longitudinal strain demonstrating subclinical LV dysfunction that increased during followup due to improved preload. 16 In the current study we had a statistically significant decline in LA and RA reservoir, conduit, and contractility phase strains and RV free wall strain. The LV global longitudinal strain also showed a decrement which was not statistically significant.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…17 A recent study published in 2020 reported reduced RV global longitudinal strain and an early decline in LV global longitudinal strain demonstrating subclinical LV dysfunction that increased during followup due to improved preload. 16 In the current study we had a statistically significant decline in LA and RA reservoir, conduit, and contractility phase strains and RV free wall strain. The LV global longitudinal strain also showed a decrement which was not statistically significant.…”
Section: Discussionmentioning
confidence: 46%
“…A recent study published in 2020 reported reduced RV global longitudinal strain and an early decline in LV global longitudinal strain demonstrating subclinical LV dysfunction that increased during follow‐up due to improved preload 16 …”
Section: Discussionmentioning
confidence: 99%